Science Student Teachers’ Independence as New Adaptation of Distance in Basic Biology Practicums - Parmin Parmin; Erna Noor Savitri; Endah Fitriani Rahayu (Jurnal Penelitian Pendidikan IPA, 2021)
The education process for science student teachers in Indonesia must continue, even in a pandemic situation with an unclear end. The research aims to find the most appropriate science practicum method during the Covid-19 pandemic for science student teachers. The method used in this research is mix-methods. The research design chosen by the researcher is the Pre-Experimental One-Group Pretest-Posttest Design. Participants in this study were 140 science student teachers who did distance practicum on basic biology practicum courses. Basic biology practicum is a practicum course that practices biological science, including respiration, photosynthesis, nutrient content of food, and pollutant testing. Based on gender, the participants were 62 male students and 78 female students. The value of N-Gain d > 0.58 (moderate effect) means that practicum activities can be continued as a practicum solution during the pandemic. Student activities during a practicum at home apply new adaptations different from a practicum in the laboratory. Independence in preparing materials and tools, preparing worksheets, simplifying materials, and modifying tools is a new way for students. The study concludes that a new practicum method that utilizes the environment potential is a solution in the implementation of science practicums as a result of the Covid-19 pandemic in Indonesia. The environment can be explored to find resources that can be used as practicum materials and the manufacture of basic biology practicum tools.